BIOPHYSICAL CHARACTERIZATION, HOST RANGE AND TRANSMISSION STUDIES OF CUCUMBER MOSAIC VIRUS - V. D. CHANDANKAR,; M. K. MONDHE,; P. R. BHOYAR,; B. N. NINAWE,; G. JADESHA, (The Bioscan, 2013)
Cucumber Mosaic Virus a ubiquitous pathogen was isolated from infected cucumber infected plants for their identification and confirmation by procedure such as biophysical properties, host range and insect transmission studies. Virus strain isolated from cucumber infected plants showed Thermal Inactivation Point (TIP) at 60ºC, Dilution End Point (DEP) in between 10-4 to 10-5 and Longevity in vitro for two days at 28ºC-30ºC and 7 days at 6ºC-8ºC temperature. During host range studies on thirty one crops of different families; eleven crops belonging to Cucurbitaceae, Compositae, Chenopodiaceae, Amaranthaceae, Leguminosae and Solanaceae family showed viral disease expression. However, inoculum failed to induce symptoms on crops belonging to Crucifereae, Caricaceae and Malvaceae. CMV under this investigation was found to be transmissible by Aphis gossypii with 100 % efficiency, followed by Aphis craccivora , Acyrthosiphum pisum , Dactynotus carthami and Aphis nerri in non - persistent manner.